Residential radon and lung cancer characteristics at diagnosis. (3rd July 2021) - Torres-Durán, María; Casal-Mouriño, Ana; Ruano-Ravina, Alberto; Provencio, Mariano; Parente-Lamelas, Isaura; Hernández-Hernández, Jesús; Vidal-García, Iria; Varela-Lema, Leonor; Valdés Cuadrado, Luis; Fernández-Villar, Alberto; Barros-Dios, Juan; Pérez-Ríos, Mónica
Abstract: Purpose: This study sought to ascertain whether there might be an association between radon concentrations and age, gender, histologic type, and tumor stage at diagnosis. Materials and methods: Lung cancer cases from different multicenter case-control studies were analyzed, and clinical data were retrieved from electronic health records and personal interviews. A radon device was placed in all dwellings of participants, and we then tested the existence of an association between residential radon and lung cancer characteristics at diagnosis. Results: Of the total of 829 lung cancer cases included, 56.7% were smokers or ex-smokers. There was no association between indoor radon concentrations and age, gender, histologic type or tumor stage at diagnosis. Median indoor radon concentrations increased with age at diagnosis for men, but not for women. When analyzing participants exposed to more than 1000 Bq/m 3, a predominance of small cell lung cancer and a higher presence of advanced stages (IIIB and IV) were observed. Conclusions: There seems to be no association between radon and age, gender, histologic type or tumor stage at diagnosis. Higher radon exposure is more frequent in the case of small-cell lung cancer.